(untitled) (Proceedings of the Global Public Health Conference, 2025)
Crime in South Africa delays progress towards universal health coverage. Universal health coverage means citizens have access to quality essential healthcare services without suffering financial hardships. The media reports about increasing violent attacks on nurses where valuable medical equipment and infrastructure at healthcare facilities are destroyed and stolen resulting in some nurses withdrawing their labour, others refusing to work after-hours leaving some facilities with inadequate staff, medicines, supplies and equipment. Violent attacks on nurses phenomenon is a complex public health issue which requires multidisciplinary solutions. This qualitative study explores and describes the impact of violent attacks on nurses through a public health and criminology lens to suggest multidisciplinary and comprehensive solutions. Data was obtained from South African online news articles, mainly Google News and Juta MedicalBrief, using key word searches such as ‘attack on nurses’ and ‘healthcare workers violence’. Retrieved news articles referred to other articles resulting in a chain-referral sampling. A thematic analysis guided by the three elements of universal health coverage was conducted, the three themes being population coverage, range of health services provided, and out-of-pocket expenditure emerged. Two criminological theories are applied to provide the possible explanation of the victimisation of nurses; these theories are the Routine Activity Theory and the Self-Control Theory. Results show that some essential services become unavailable, some facilities stop operating during the evenings and over weekends, which forces patients to spend money to access services far from where they reside and, in the process, suffer financial hardships. Crime is reported to be high in South Africa and affects everyone. The media increasingly reports about violent attacks on nurses. These attacks retards progress towards achievement of universal health coverage as it affects availability of nurses, negatively leading to unavailability of services at affected facilities. Patients are then forced to travel long distances to access healthcare services elsewhere. The media raises public awareness on this challenge, and this should spur a joint action to develop comprehensive solutions. Based on the Routine Activity Theory, the authors argue that nurses are victimised in public healthcare facilities because of the convergence of three elements which are the motivated offender, a suitable target, and a lack of capable guardian. The capable guardian could be the security personnel or other workers to intervene during the criminal victimisation. Applying the Self-Control Theory to explain victimisation of nurses, the authors put forth that perpetrators who victimise nurses are low in self-control and are in pursuit of immediate, easy and short-term pleasure. As such, they insult, physical manhandle nurses or steal from them, without considering that they may be punished for their actions.